Writing a research proposal - Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2014)
A research proposal is an important process of any research. The success of any research is depending on the quality of research proposal. The science and art of writing a research proposal depending on several factors, these include the time deadlines, quality benchmarks and associated costs. A research proposal should provide an overview of research, it gives the reader sufficient information about the research work, the complete work plan, the value and the scope of the research. A research proposal does not only communicates what researchers are trying to accomplish, but is also a tool for researchers to obtaining research fund. There are no specific rules on structure or format on writing a research proposal – it is depend on institution, funding agency and supervisor of thesis or dissertation. A research proposal may refine as the research on progress – it is not uncommon when comes to the final submission it might be a totally different document. Aim of this paper is to provide some guides and tips on writing a research proposal to new researchers, as well undergraduate or post graduate students.